LINQ quickly a practical guide to programming language integrated query with C# - Kumar, N. Satheesh; Safari eBooks (Birmingham, U.K. : Packt Pub., 2007)
"This book gets you started with LINQ and shows how it will make your programming life easier by making use of new features from the .NET Framework 3.0. This book is split into seven chapters, each of which is dedicated to presenting a feature of LINQ and its usage in real-life scenarios. Language Integrated Query (LINQ) is a new feature in Visual Studio 2008 that extends its query capabilities, using C# and Visual Basic. Visual Studio 2008 comes with LINQ provider assemblies that enable the use of LINQ with data sources such as in-memory collections, SQL relational databases, ADO.NET Datasets, XML documents, etc"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Query languages (Computer science); Microsoft Visual studio; Microsoft Visual BASIC; Microsoft .NET Framework; C# (Computer program language); Electronic books